Street Theater in Modern Media Space - A. Semenova, E.; ., . (International Journal of Engineering and Technology, 2018)
Street theater is viewed in modern media space as a reduced, repeatedly duplicated carnival area. M.M. Bakhtinâ€™s understanding of reduced forms of carnival laughter, which include humor, irony, sarcasm, is applied. The modern festival movement of street theaters in the beginning of the 21st century is analyzed. It is proved that despite the fact that street theater actively uses new interactive means of media communication, containing various information (audio-visual, acoustic, computing, optical, imagery, artistic, scenic, etc.) and contributing to the acceleration of information dissemination and audience expansion, this form of theater is rapidly degenerating. Street theater is transformed into a serious socio-cultural game. But despite the fact that media technologies offer not excess but poverty (deficit) instead of extravagant human nature, the carnival origin is preserved not in replicable formats of street theater, but in informal communication between urban and rural youth. This makes it possible to talk about the preservation of modern man's vital need for street theater and carnival communication. The analysis of these issues is based on the views of M.M. Bakhtin, V.B. Shklovsky, Guy Debord, and J. Baudrillard.Â Â